Meningkatkan Profesional Guru dengan Program Pendidikan Profesi Guru (PPG) - Iqbal Maulana; Nia Atikah Rahma; Namira Fitri Mahfirah; Wahyu Alfarizi; Ahmad Darlis (Departement of Mathematics Education, 2023)
The development of professional teachers is protected by the Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers and Government Regulation of the Republic of Indonesia Number 74 of 2008 concerning Teacher Certification. Educator certification for teachers is obtained through professional education programs organized by tertiary institutions that have programs for procuring accredited education staff, both those held by the government and the community, which are then determined by the government. The research was conducted using a qualitative descriptive approach because it describes events. According to (Arikunto, 2006)